Cloning, preparation and preliminary crystallographic studies of penicillin V acylase autoproteolytic processing mutants - Chandra, P. M.; Brannigan, James A.; Prabhune, Asmita; Pundle, A.; Turkenburg, J. P.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2005)

Cloning, purification, crystallization and preliminary structural studies of penicillin V acylase from Bacillus subtilis - Rathinaswamy, P.; Pundle, A. V.; Prabhune, Asmita; SivaRaman, H.; Brannigan, James A.; Dodson, Guy G.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology Communications, 2005)
{Penicillin acylase proteins are amidohydrolase enzymes that cleave penicillins at the amide bond connecting the side chain to their beta-lactam nucleus. An unannotated protein from Bacillus subtilis has been expressed in Escherichia coli, purified and confirmed to possess penicillin V acylase activity. The protein was crystallized using the hanging-drop vapour-diffusion method from a solution containing 4 M sodium formate in 100 mM Tris-HCl buffer pH 8.2. Diffraction data were collected under cryogenic conditions to a spacing of 2.5 A. The crystals belonged to the orthorhombic space group C222(1), with unit-cell parameters a = 111.0

Preparation and characterization of a copper based Indian traditional drug: tamra bhasma - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2005)
The copper based Indian traditional drug `tamra bhasma' is administered for various ailments since long. Its synthesis involves treating metallic copper with plant juices and then repeated calcination in presence of air so that the metallic state is transformed into the corresponding oxide form traditionally known as `bhasma'. In this work, we present a systematic characterization of this traditional drug using various techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM)-energy dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy (XPS), infrared spectroscopy (IR), thermogravimetry (TG) and surface area measurement. The results obtained were found to match very well with those of a standard copper oxide confirming the composition of the drug sample. In addition, some specific findings were also made which could help in interpreting the therapeutic properties of the traditional drug `tamra bhasma'. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: copper oxide; crystallite size; tamra bhasma; traditional medicine; XPS of copper oxide; XRD

Effect of calcination cycles on the preparation of tin oxide based traditional drug: studies on its formation and characterization - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Gaikwad, A. B.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2006)
The preparation method of metal based Indian traditional drugs involves conversion of a pure metal into its oxide by repeated high temperature calcination cycles. In this work, the effect of number of calcination cycles followed in the preparation of tin oxide based Ayurvedic drug, `vanga bhasma' was studied by a systematic characterization of the drug samples after various calcination stages. It was found that tin was in the form of Sn4+ state and that the formation of SnO2 proceeded step-wise through Sn(OH)(4). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: calcination cycles; Oxidation; oxidation state of tin; Particle size; tin oxide; vanga bhasma

Structural and functional analysis of a conjugated bile salt hydrolase from Bifidobacterium longum reveals an evolutionary relationship with penicillin V acylase - Kumar, R. Suresh; Brannigan, James A.; Prabhune, Asmita; Pundle, Archana V.; Dodson, Guy G.; Dodson, Eleanor J.; Suresh, C. G. (Journal of Biological Chemistry, 2006)
Bile salt hydrolase (BSH) is an enzyme produced by the intestinal microflora that catalyzes the deconjugation of glycine- or taurine-linked bile salts. The crystal structure of BSH reported here from Bifidobacterium longum reveals that it is a member of N-terminal nucleophil hydrolase structural superfamily possessing the characteristic alpha beta beta alpha tetra-lamellar tertiary structure arrangement. Site-directed mutagenesis of the catalytic nucleophil residue, however, shows that it has no role in zymogen processing into its corresponding active form. Substrate specificity was studied using Michaelis-Menten and inhibition kinetics and fluorescence spectroscopy. These data were compared with the specificity profile of BSH from Clostridium perfrigens and pencillin V acylase from Bacillus sphaericus, for both of which the three-dimensional structures are available. Comparative analysis shows a gradation in activity toward common substrates, throwing light on a possible common route toward the evolution of pencillin V acylase and BSH.

Bacterial enzyme mediated biosynthesis of gold nanoparticles - Bharde, Atul A.; Kulkarni, Aarohi; Rao, Mala; Prabhune, Asmita; Sastry, Murali (Journal of Nanoscience and Nanotechnology, 2007)
Development of synthesis methods for anisotropic metal nanoparticles is of considerable interest due to their remarkable optoelectronic properties. Various shapes ranging from rods to cubes to tetrapods and prisms may be obtained by chemical methods. Here we show that anisotropic gold nanoparticles can be synthesized biologically by the bacterium Actinobacter spp. when challenged with gold chloride in the presence of Bovine serum albumin (BSA). We also observed that synthesis of gold nanoparticles occur with simultaneous induction of the protease enzyme secreted by the bacterium in the presence of BSA. The presence of BSA helps to enhance the rate of gold nanoparticles biosynthesis and may also impart some shape control. Controlling simple experimental conditions like incubation temperature and presence or absence of oxygen have drastic effect on the reaction rate and the morphology of the particles. Various assay experiments show that the presence of enzyme protease can act as a reducing as well as shape directing agent.
Keywords: Biosynthesis; bovine serum; gold nanoparticles

Cephalexin-mediated synthesis of quasi-spherical and anisotropic gold nanoparticles and their in situ capping by the antibiotic - Jagannathan, Ramya; Poddar, Pankaj; Prabhune, Asmita (Journal of Physical Chemistry C, 2007)
Here we report, for the first time, synthesis of gold nanostructures in aqueous medium by reducing gold ions using cephalexin, a potent broad-spectrum antibiotic, where the morphology of the gold nanoparticles is found to be dependent on the concentration of chloroauric acid. The characterization techniques indicate that particle surfaces are coated with the robust layer of the antibiotic making them stable for a long time. Thus, cephalexin acts as both the reducing and the capping agent. NMR and XPS analysis indicate that the sulfur moiety is responsible for the reduction and binding process.

Immobilization of Ntn hydrolases on APTES fuctionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (From Zeolites to Porous Mof Materials: the 40th Anniversary of International Zeolite Conference, Proceedings of the 15th International Zeolite Conference, 2007)
APTES Functionalized mesoporous silica SBA-15 molecular sieves have been prepared and used for immobilization of Penicillin G acylase. Physico chemical characterization was done by nitrogen adsorption, powder XRD and TEM methods to understand the nature of immobilized PGA enzyme. XRD data indicate a good mesoscopic order. The characteristic hexagonal features of SBA-15 were maintained in PGA immobilized SBA-15 samples. Incorporation of PGA does not affect the original pore structure of the parent SBA-15. The adsorption of PGA on SBA-15 from buffered solutions with a pH value, 7.8 has been studied as a model protein adsorption system. The maximum activity of the immobilized enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The stability of Penicillin G acylase was enhanced by the physical entrapment in SBA-15.

Multiutility sophorolipids as nanoparticle capping agents: synthesis of stable and water dispersible Co nanoparticles - Kasture, Manasi; Singh, Sanjay; Patel, Pitamber; Joy, Pattayil Alias; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (Langmuir, 2007)
Sophorolipids are a class of glycolipids that can be obtained from fatty acids by simply treating them with yeast cells (Candida bombicola, ATCC 22214) and glucose. In this letter, we demonstrate the application of sophorolipids obtained from oleic acid as a capping agent for Co nanoparticles. Upon capping the nanoparticle surface, the sugar moiety of these sophorolipids is exposed to the solvent environment, making the nanoparticles stable and water-redispersible.

Purification by silica gel chromatography using dialysis tubing and characterization of sophorolipids produced from Candida bombicola grown on glucose and arachidonic acid - Shah, Sachin; Prabhune, Asmita (Biotechnology Letters, 2007)
The yeast Candida bombicola (ATCC 22214) grown on primary carbon source glucose (100 g l(-1)) and secondary carbon, arachidonic acid (2 g l(-1)) produced mixture of sophorolipids up to 1.44 g l(-1). The crude product was a heterogeneous mixture of sophorolipids, which are glycolipids of sophorose linked to the fatty acid through glycosidic bond between omega and omega-1 carbon of arachidonic acid. The derived sophorolipids were isolated by silica gel chromatography using dialysis tubing. The purified sophorolipids were characterized by ESI-MS and FT-IR. Acid hydrolysis of the resolved sophorolipids were characterized by ESI-MS for the presence of 20-hydroxy-5Z,8Z,11Z,14Z-eicosatetraenoic acid (20-HETE) and 19-hydroxy-5Z,8Z,11Z,14Z-eico-satetraenoic acid (19-HETE), compounds of pronounced pharmaceutical importance.
Keywords: 19-HETE; 20-HETE; arachidonic acid; electrospray soft ionization mass spectroscopy; silica gel chromatography; Sophorolipid

Tryptophan residue is identified in the substrate binding of penicillin G acylase from Kluyvera citrophila - Kumar, R. Suresh; Prabhune, Asmita; Pundle, A. V.; Karthikeyan, Muthukumarasamy; Suresh, C. G. (Enzyme and Microbial Technology, 2007)
Penicillin acylases are important enzymes in pharmaceutical industry for the production of semi-synthetic beta-lactam antibiotics via the key intermediate 6-aminopenicillanic acid. The penicillin G acylase purified from Kluyvera citrophila (KcPGA) on modification with tryptophan-specific reagents such as N-bromo succinamide (NBS) and 2-hydroxy 5-nitrobenzylbromide (HNBB) showed partial loss of activity and substrate protection. Various solute quenchers and substrate were used to probe the microenvironment of the putative reactive tryptophan through fluorescence quenching. Homology modeling of KcPGA structure has been carried out. Docking substrate on this modeled KcPGA structure identifies the tryptophan residue that is directly influenced by substrate binding. To confirm the biological significance of this particular tryptophan, we did a sequence comparison of PGAs from various organisms. The sequence alignment clustered the matches into two sets, those closer to (> 40% identical) KcPGA and had the tryptophan of interest present in them formed the first set, while those less identical (< 30%) to KcPGA and the particular tryptophan absent in them formed the second set. It is clear from the reported kinetic parameters of representative members of these two sets that the affinity for penicillin G (penG) of the former class is several times better. Thus, based on our studies we suggest that the tryptophan residue in the identified position is important for binding substrate penG by the acylases. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: fluorescence measurement; K. citrophila; Penicillin G acylase; sequence alignment; substrate-docking; tryptophan modification

Characterization of smallest active monomeric penicillin V acylase from new source: a yeast, rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Prabhune, Asmita; Suresh, C. G.; Pundle, Archana (Process Biochemistry, 2008)
An intracellular monomeric penicillin V acylase (PVA) of 36,000 Da exhibiting pI of 4.19, purified from newly identified yeast source, Rhodotorula aurantiaca (NCIM 3425). The enzyme was purified by hydrophobic interaction chromatography. The enzyme showed optimal activity at 45 degrees C and retained 80% activity after incubation at 45 degrees C and pH 5.5 for I h. The enzyme showed maximum activity at pH 5.5 and was very stable between pH 5.5-6.5 with optimum stability at pH 6.0. It exhibited 50% of its original activity after 30 min incubation at 60 degrees C. Enzyme hydrolyzed substrates with benzyl side chain but preferred penicillin V as primary substrate. N-terminally located serine supports the fact that it belongs to Ntn (N-terminal nucleophile)-hydrolase superfamily. The initial ten amino acid residues of R. aurantiaca PVA were identical to the initial sequence of NADH dehydrogenase (EC 1.6.99.3): however the enzyme lacks dehydrogenase activity. EGTA, EDTA, hexane and ethyl acetate stabilized the activity where as small chain alcohols inhibited it. 1,4-Dioxane, THF (tetrahydrofurane), phenol and benzyl alcohol severely inhibited enzyme activity while BME and DTT increased it. Tween 80 and Tween 20 highly enhanced the activity where as SIDS and Triton X-100 inhibited it. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Intracellular enzyme; N-terminal sequencing; Penicillin V acylase; Purification; Rhodotorula aurantiaca; Substrate specificity

COLL 41-studies in biosurfactants: sophorolipids - Momin, Shamim A.; Prabhune, Asmita; Sonchal, Bhushan P.; Shah, Sachin; Kothekar, Shrinivas C. (235th American-Chemical-Society National Meeting, 2008)
Keywords: Biosurfactants; Candida bombicola ATCC 22214; Fermentation Process; sophorolipids

In situ synthesis of ligand reduced/capped silver nanoparticles and the effect of temperature and ligand structure on the size of silver nanoparticles - Kasture, M. B.; Patel, P.; Prabhune, Asmita; Ramana, C. V.; Kulkarni, A. A.; Bhagavatula L. V. Prasad (Journal of Chemical Sciences, 2008)
We report in situ synthesis of silver nanoparticles using biosurfactants called sophorolipids as reducing and capping agents. We further study the effect of temperature and the structure of sophorolipid on the size of silver nanoparticles obtained. The silver nanoparticles were characterized by UV-visible, transmission electron microscope (TEM) and light scattering (DLS) analysis techniques.
Keywords: dynamic light scattering; Nucleation and growth; silver nanoparticles; Sophorolipid

Structural features of Penicillin acylase adsorption on APTES functionalized SBA-15 - Shah, Pallavi; Sridevi, N.; Prabhune, Asmita; Ramaswamy, Veda (Microporous and Mesoporous Materials, 2008)
The immobilization of Penicillin acylase (PGA) enzyme (which belongs to the Ntn hydrolase super family) into the amino-functionalized SBA-15 mesoporous molecular sieve is carried out to see the effect of silica as a host matrix on the enzyme kinetics. Physicochemical characterization by nitrogen adsorption, powder XRD and TEM methods indicate that the characteristic hexagonal features and the original pore structure of the parent SBA-15 is retained even after the incorporation of PGA. The adsorption of PGA on SBA15 shows a dependence on the pore volume and the composition of the adsorbent. The maximum loading of the enzyme was observed at pH 7.8, slightly below the isoelectric point of the enzyme. The loading capacity of immobilized PGA is 34 mg protein per 0.5 g of SBA-15. The trapped enzyme is more stable than the soluble form to temperature and pH environments and retained 73% of its activity after immobilization. This enhanced stability is attributed to the protective nature of the cage itself and to the rigidity of the SiO(2) matrix, which reduces the freedom of peptide-chain refolding of molecular motions that occur in denaturation processes. The strength of binding is very strong; however, the activity of the immobilized enzyme is then simply restored with very little leakage of enzyme from the support. An important feature of the immobilized PGA enzyme is the excellent reusability without significant loss in activity, which indicates potentially exciting industrial/biomedical application of this support. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Penicillin G acylase; PGA immobilized SBA-15; pH and temperatures stability; SBA-15

Brevibacillus sp: a novel thermophilic source for the production of bile salt hydrolase - Sridevi, N.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2009)
A thermophilic microorganism growing within the temperature range of 40-65 A degrees C (optimum at 55 A degrees C) was isolated from hot water springs near Konkan, Maharashtra, India. Based on 16S rDNA sequence analysis, it was concluded that the isolate belongs to the genus Brevibacillus. The present paper reports the isolation, identification, and standardization of fermentation conditions for the production of enzyme, bile salt hydrolase (EC 3.5.1.24) which is produced intracellularly at high temperatures. This is the first report regarding the production of bile salt hydrolase from a thermophilic source. Optimization of fermentation conditions resulted in a 2.9-fold enhancement in enzyme production.
Keywords: Bile salt hydrolase; Brevibacillus sp; Fermentation; Glycodeoxycholic acid; Hot springs; Thermophile

Direct method for the preparation of glycolipid-metal nanoparticle conjugates: sophorolipids as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles and their antibacterial activity - Singh, Sanjay; Patel, Pitamber; Jaiswal, Swarna; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2009)
The production of a new class of glycolipid-metal nanoparticle conjugates, namely, sophorolipid reduced/capped silver nanoparticles is demonstrated for the first time, by unveiling the reducing and capping abilities of sophorolipid derived from oleic acid. It is also demonstrated that the sophorolipid capped Ag nanoparticles are highly potent antibacterial agents, against both Gram-positive and Gram-negative bacteria. The utilization of sophorolipid brings out several advantages, such as eliminating the necessity for exogenous reducing agent and imparting better stability to the silver nanoparticles as compared to their oleic acid capped analogues. These sophorolipid capped silver nanoparticles can be obtained as a stable powder that can be re-dispersed in water as desired.

Effect of cultural conditions and media constituents on production of penicillin V acylase and CTAB treatment to enhance whole-cell enzyme activity of rhodotorula aurantiaca (NCIM 3425) - Kumar, Atul; Singh, Sanjay; Poddar, Pankaj; Prabhune, Asmita; Pundle, Archana (Applied Biochemistry and Biotechnology, 2009)
Penicillin V acylase (PVA) is a pharmaceutically important enzyme as it plays a vital role in the manufacture of semi-synthetic beta-lactam antibiotics. Rhodotorula aurantiaca (NCIM 3425) produced high levels of intracellular penicillin V acylase after 18 h at pH 8.0 and temperature 27 degrees C. Fructose was the best carbon source for PVA production, whereas tryptone was the best nitrogen source to produce the enzyme up to 170 and 1,088 IU/l of culture, respectively. Additionally, the cell-bound PVA activity was enhanced on treatment with cationic detergent. Whole-cell activity was found to be doubled (204%) on treatment of 0.01 g dry weight of cells with 50 mu g/ml solution of N-cetyl-N,N,N-trimethylammoniumbromide at pH 8.0 for 1 h at room temperature. Atomic force microscopy images of permeabilized cells show perturbation in the cell wall and offer first-ever visual illustration of surface structure modifications that occur during permeabilization of R. aurantiaca cells leading to enhancement in activity of intracellular enzyme.
Keywords: Atomic force microscopy; Intracellular enzyme; Penicillin Vacylase; Permeabilization; Rhodotorula aurantiaca

Hypocholesteremic effect of bile salt hydrolase from Lactobacillus buchneri ATCC 4005 - Sridevi, N.; Vishwe, Pradnya; Prabhune, Asmita (Food Research International, 2009)
The effect of oral administration of the immobilized bile salt hydrolase enzyme on serum cholesterol. triglyceride, high density lipoprotein levels and its application in the therapeutic treatment of hypercholesteremia was assessed. Culture conditions were optimized for the production of bile salt hydrolase, which resulted in 2.9-fold enhancement in activity. Bile salt hydrolase (BSH; E.C.3.5.1.24) was isolated from Lactobacillus buchneri ATCC 4005 and immobilized in 0.5% gellan gum gel. The immobilized enzyme was orally delivered in wistar rats, induced with hypercholesteremia by triton X-100. The serum cholesterol and triglycerides were reduced by 50% and 15%, respectively, in the group fed with immobilized enzyme 10 IU/kg dose whereas administration of 20 IU/kg immobilized enzyme resulted in reduction of serum cholesterol by 58% and triglycerides by 45%, respectively. The results indicate that bile salt hydrolase has potential cholesterol lowering property and oral administration of the immobilized enzyme is an alternative pharmacological approach to reduce serum cholesterol levels. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Bile salt hydrolase; Gellan gum; Hypocholesteremic effect; Lactobacillus buchneri; Wistar Rats

In situ observation of antibiotic mediated concurrent growth of two distinct homogeneous populations of gold nanoparticles in solution phase - Jagannathan, Ramya; Parmar, Avanish Singh; Adyanthaya, Suguna D.; Prabhune, Asmita; Muschol, Martin; Poddar, Pankaj (Journal of Physical Chemistry C, 2009)
We report the observation of the unusual nucleation and growth kinetics of gold nanoparticles synthesized in the presence of the antibiotic cephalexin using in situ static and dynamic light scattering in conjunction with in situ UV-vis absorption measurements and transmission electron microscopy. Following a brief latency period, two well-separated populations of gold nanoparticles, with average sizes of 1-2 nm versus several tens of nanometer, respectively, nucleate simultaneously. For either size regime, the total number of particles increased rapidly, while their mean size and relative frequency remained essentially constant over a growth period of 5 h. With increasing temperature, the morphology of the larger nanoparticles became increasingly spherical, as indicated by the noticeable blue shift of the plasmon frequency for these particles. The detailed morphology for either particle population was confirmed with TEM. To our knowledge, this is the first observation of simultaneous growth of two distinct populations of crystalline nanoparticles in the solution phase. The coupled growth of two distinct populations of nuclei, their tight control of size but rapid increase in overall numbers present novel and intriguing facets of this antibiotic-mediated solution-growth of gold nanoparticles. The size evolution of the Mie-frequency exhibits a noticeable blue shift as the temperature increases, correlating with the roundness of the particle/bimodal distribution.

Antibiotic mediated synthesis of gold nanoparticles with potent antimicrobial activity and their application in antimicrobial coatings - Rai, Akhilesh; Prabhune, Asmita; Perry, Carole C. (Journal of Materials Chemistry, 2010)
We report a one-pot synthesis of spherical gold nanoparticles (52-22 nm) and their capping with cefaclor, a second-generation antibiotic, without use of other chemicals. The differently sized gold nanoparticles were fabricated by controlling the rate of reduction of gold ions in aqueous solution by varying the reaction temperature (20-70 degrees C). The primary amine group of cefaclor acted as both the reducing and capping agent for the synthesis of gold nanoparticles leaving the beta-lactam ring of cefaclor available for activity against microbes. Antimicrobial testing showed that cefaclor reduced gold nanoparticles have potent antimicrobial activity against both Gram-positive (Staphylococcus aureus) and Gram-negative (Escherichia coli) bacteria as compared to cefaclor or gold nanoparticles alone. The minimum inhibition concentrations (MICs) of cefaclor reduced gold nanoparticles were 10 mu g mL(-1) and 100 mu g mL(-1) for S. aureus and E. coli respectively. The cefaclor reduced gold nanoparticles were further coated onto poly(ethyleneimine) (PEI) modified glass surfaces to obtain antimicrobial coatings suitable for biomedical applications and were tested against E. coli as an exemplar of activity. The antimicrobial coatings were very robust under adverse conditions (pH 3 and 10), inhibited the growth of E. coli on their surfaces, and could be used many times with retained activity. Results from a combined spectroscopic (FTIR) and microscopic study (AFM) suggest that the action of these novel particles is through the combined action of cefaclor inhibiting the synthesis of the peptidoglycan layer and gold nanoparticles generating ``holes'' in bacterial cell walls thereby increasing the permeability of the cell wall, resulting in the leakage of cell contents and eventually cell death.

Biocatalytic approach for the utilization of hemicellulose for ethanol production from agricultural residue using thermostable xylanase and thermotolerant yeast - Menon, Vishnu; Prakash, Gyan; Prabhune, Asmita; Rao, Mala (Bioresource Technology, 2010)
A hydrolysis of 62% and 50% for OSX (Oat spelt xylan) and WBH (Wheat bran hemicellulose) were obtained in 36 h and 48 h using Accellerase(TM) 1000 at 50 degrees C wherein thermostable xylanase from alkalothermophilic Thermomonospora sp. yielded 67% (OSX) in 3 h and 58% (WBH) in 24 h at 60 degrees C, favouring a reduction in process time and enzyme dosage. The rate of hydrolysis with thermostable xylanase was increased by 20% with the addition of nonionic surfactant tween 80 or biosurfactant sophorolipid. The simultaneous saccharification and fermentation (SSF) of OSX and WBH using thermostable xylanase and D. hansenii in batch cultures produced 9.1 g/L and 9.5 g/L of ethanol, respectively and had a shorter overall process time than the separate hydrolysis and fermentation (SHF). The immobilized yeast cells in Ca-alginate matrix produced ethanol with a yield of 0.46 g/g from hemicellulosic hydrolysates and were reused six times with 100% fermentation efficiency. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biosurfactant; Ethanol; Hemicellulose; Thermostable xylanase; Thermotolerant yeast

Continuous flow synthesis of functionalized silver nanoparticles using bifunctional biosurfactants - Kumar, D. V. Ravi; Kasture, Manasi; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Green Chemistry, 2010)
Silver nanoparticles were synthesized by continuous flow methods using biosurfactants, namely, oleic acid sophorolipid (OASL) and stearic acid sophorolipid (SASL). Both the sophorolipids can act as reducing and capping agents. The effect of temperature on the completion of nanoparticle formation and the particle growth dynamics (size) were studied in batch mode. While the completion of the reaction using oleic acid sophorolipid needed 20 min, only 5 min were required with the stearic acid sophorolipid as capping and reducing agent. Hence all the continuous flow experiments were carried out using the stearic acid sophorolipid. The continuous flow synthesis of silver nanoparticles was carried out in a stainless steel helical coil and also in a spiral polymeric minichannel reactor. The DLS results show that higher flow rate leads to the formation of bigger and polydisperse particles because of incomplete reactions. Higher residence time allowed the completion of reaction leading to spherical, small and monodisperse particles.

Cytotoxic and genotoxic assessment of glycolipid-reduced and -capped gold and silver nanoparticles - Singh, Sanjay; D'Britto, Virginia; Prabhune, Asmita; Ramana, C. V.; Dhawan, Alok; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
A systematic cytotoxic and genotoxic evaluation of glycolipid-conjugated silver and gold nanoparticles is carried out. These glycolipid nanoparticle conjugates are obtained by exploiting the reductive capability of a class of glycolipids called sophorolipids that play the role of capping agent as well. Further, when tested for their cytotoxicity and genotoxicity on HepG2 cells, these nanoparticles are found to be cytocompatible up to 100 mu M metal concentrations. Of the two metallic systems investigated, gold nanoparticles are found to be more cytocompatible than the same concentrations of silver nanoparticles. Similarly, it is also demonstrated that at 100 mu M, silver nanoparticles cause more DNA damage compared to gold nanoparticles of similar concentrations.

Cytotoxicity of sophorolipid-gellan gum-gold nanoparticle conjugates and their doxorubicin loaded derivatives towards human glioma and human glioma stem cell lines - Dhar, Sheetal; Reddy, E. Maheswara; Prabhune, Asmita; Pokharkar, Varsha; Shiras, Anjali; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Biocompatible gold nanoparticles were synthesized by using a naturally occurring gum-Gellan Gum-as a capping and reducing agent. These were further conjugated with sophorolipids which again were accessed through a biochemical transformation of a fatty acid. The cellular uptake of sophorolipid-conjugated gellan gum reduced gold nanoparticles and their cytotoxicity on human glioma cell line LN-229 and human glioma stem cell line HNGC-2 were investigated. Quite surprisingly even the simple sophorolipid-conjugated gellan gum reduced/capped gold nanoparticles showed greater efficacy in killing the glioma cell lines and, gratifyingly, the glioma stem cell lines also. The cytotoxic effects became more prominent once the anti cancer drug doxorubicin hydrochloride was also conjugated to these gold nanoparticles.

Differentiation-inducing ability of sophorolipids of oleic and linoleic acids using a glioma cell line - Joshi-Navare, Kasturi; Shiras, Anjali; Prabhune, Asmita (Biotechnology Journal, 2011)
Sophorolipids are biosurfactants produced by non-pathogenic yeasts. They show structural similarity with the membrane components of mammalian cells, i.e., glycosphingolipids and gangliosides, which are involved in processes such as signaling, oncogenesis, and differentiation. Sophorolipids have been reported to induce differentiation in several leukemic cell lines, cell death via apoptosis in a human liver cancer cell line, and necrosis in a pancreatic adenocarcinoma cell line. Here we report, for the first time, the effects of precursor fatty acids and sophorolipids of oleic and linoleic acids in pure acidic and crude forms on LN-229, a glioma cell line. In response to different sophorolipid forms, various morphological changes were observed, such as formation of long thread-like extensions arising from the ends of the cells, cell alignment, cell elongation and bundle formation in a dose-dependent manner. In this study we present the morphological evidence of the potential of sophorolipids as differentiation inducers.
Keywords: Differentiation; Glioma; LN-229; Sophorolipid

Isolation, identification and optimization of a new extracellular lipase producing strain of rhizopus sp. - Kantak, Jayshree B.; Bagade, Aditi V.; Mahajan, Siddharth A.; Pawar, Shrikant P.; Shouche, Yogesh S.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2011)
A lipolytic mesophilic fungus which produces lipase extracellularly was isolated from soil. Based on ITS1-5.8S-ITS4 region sequences of ribosomal RNA, it was concluded that the isolate JK-1 belongs to genus Rhizopus and clades with Rhizopus oryzae. The present paper reports the screening, isolation, identification, and optimization of fermentation conditions for the production of lipase (EC 3.1.1.3). Culture conditions were optimized, and the highest lipase production was observed in basal medium with corn steep liquor as nitrogen source and glucose as carbon source. Maximum lipase production was observed at 72 h, which is about 870 U/ml. Optimization of fermentation conditions resulted in 16-fold enhancement in enzyme production.
Keywords: Corn steep liquor; Fermentation; ITS region; Lipase; Medium optimization; Rhizopus

Microbial production of xylitol from D-xylose and sugarcane bagasse hemicellulose using newly isolated thermotolerant yeast Debaryomyces hansenii - Prakash, Gyan; Varma, Anjanikumar; Prabhune, Asmita; Shouche, Yogesh; Rao, Mala (Bioresource Technology, 2011)
A thermotolerant yeast capable of fermenting xylose to xylitol at 40 C was isolated and identified as a strain of Debaryomyces hansenii by ITS sequencing. This paper reports the production of xylitol from D-xylose and sugarcane bagasse hemicellulose by free and Ca-alginate immobilized cells of D. hansenii. The efficiency of free and immobilized cells were compared for xylitol production from D-xylose and hemicellulose in batch culture at 40 degrees C. The maximum xylitol produced by free cells was 68.6 g/L from 100 g/L of xylose, with a yield of 0.76 g/g and volumetric productivity 0.44 g/L/h. The yield of xylitol and volumetric productivity were 0.69 g/g and 0.28 g/L/h respectively from hemicellulosic hydrolysate of sugarcane bagasse after detoxification with activated charcoal and ion exchange resins. The Ca-alginate immobilized D. hansenii cells produced 73.8 g of xylitol from 100 g/L of xylose with a yield of 0.82 g/g and volumetric productivity of 0.46 g/L/h and were reused for five batches with steady bioconversion rates and yields. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Immobilization; Sugarcane bagasse hemicellulose; Thermotolerant Debaryomyces hansenii; xylitol; Xylose

Silver nanoparticle studded porous polyethylene scaffolds: bacteria struggle to grow on them while mammalian cells thrive - D'Britto, Virginia; Kapse, Harsha; Babrekar, Harshada A.; Prabhune, Asmita; Bhoraskar, S. V.; Premnath, V.; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Silver nanoparticle studded scaffolds were prepared by exploiting the Ag+ ion reducing activity of sophorolipids-a class of `glycolipids' that cap the ensuing nanoparticles as well. To achieve this, the porous polyethylene scaffolds are subjected to N-2+H-2 plasma treatment, in the first step. Subsequently the sophorolipids are covalently attached to the amine groups on the polymer surface through simple amide chemistry to yield sophorolipid grafted polymer scaffolds. These are then exposed to Ag+ ions under appropriate conditions leading to the formation of silver nanoparticles immobilized on the polymer scaffolds. It has been found that while bacteria do not survive on these silver studded scaffolds, CHO-K1 cells thrive on them making them good candidates for tissue engineering and bio-implant applications.

Characterization of smallest active monomeric lipase from novel rhizopus strain: application in transesterification - Kantak, Jayshree B.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2012)
An extracellular lipase-producing fungus was isolated from oil-rich soil. This fungus belongs to the genus Rhizopus and clades with Rhizopus oryzae. Lipase was purified to homogeneity from this novel fungal source using ammonium sulphate precipitation followed by Q-Sepharose chromatography. The extracellular lipase was purified 8.6-fold, and enzymatic properties were studied. The molecular mass of the purified enzyme was estimated to be 17 kD by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and 16.25 kD by matrix-assisted laser desorption ionization/time-of-flight analysis. The native molecular mass was estimated to be 17.5 kD by gel filtration, indicating the protein to be monomer. The optimum pH and temperature for the enzyme catalysis were 7.0 A degrees C and 40 A degrees C, respectively. Enzyme was stable in pH range 6.0-7.0 and retains 95-100% activity when incubated at 50 A degrees C for 1 h. The pI of the purified lipase was 4.2. Enzyme was stable in the organic solvents such as ethanol, hexane and methanol for 2 h. Purified enzyme was used for transesterification of oleic acid in the presence of ethanol for production of oleic acid ethyl ester with a conversion efficiency of 66% after 24 h at 30 A degrees C.
Keywords: Lipase; Low molecular weight; Purification; Rhizopus; transesterification

Crystallization and X-ray structure analysis of a thermostable penicillin G acylase from alcaligenes faecalis - Varshney, Nishant Kumar; Kumar, R. Suresh; Ignatova, Zoya; Prabhune, Asmita; Pundle, Archana; Dodson, Eleanor J.; Suresh, C. G. (Acta Crystallographica Section F-Structural Biology and Crystallization Communications, 2012)
{The enzyme penicillin G acylase (EC 3.5.1.11) catalyzes amide-bond cleavage in benzylpenicillin (penicillin G) to yield 6-aminopenicillanic acid, an intermediate chemical used in the production of semisynthetic penicillins. A thermostable penicillin G acylase from Alcaligenes faecalis (AfPGA) has been crystallized using the hanging-drop vapour-diffusion method in two different space groups: C2221, with unit-cell parameters a = 72.9
Keywords: calcium binding; disulfide bridges; Ntn hydrolases; orthorhombic form; tetragonal form; Thermostability

Purification and characterization of YxeI, a penicillin acylase from Bacillus subtilis - Rathinaswamy, Priya; Gaikwad, Sushama M.; Suresh, C. G.; Prabhune, Asmita; Brannigan, James A.; Dodson, Guy G.; Pundle, Archana V. (International Journal of Biological Macromolecules, 2012)
The paper reports the purification and characterization of the first penicillin acylase from Bacillus subtilis. YxeI, the protein annotated as hypothetical, coded by the gene yxeI in the open reading frame between iol and hut operons in B. subtilis was cloned and expressed in Eshcherichia coli, purified and characterized. The purified protein showed measurable penicillin acylase activity with penicillin V. The enzyme was a homotetramer of 148 kDa. The apparent Km of the enzyme for penicillin V and the synthetic substrate 2-nitro-5-(phenoxyacetamido)-benzoic acid was 40 mM and 0.63 mM, respectively, and the association constants were 8.93 x 10(2) M-1 and 2.51 x 10(5) M-1, respectively. It was inhibited by cephalosporins and conjugated bile salts, substrates of the closely related bile acid hydrolases. It had good sequence homology with other penicillin V acylases and conjugated bile acid hydrolases, members of the Ntn hydrolase family. The N-terminal nucleophile was a cysteine which is revealed by a simple removal of N-formyl-methionine. The activity of the protein was affected by high temperature, acidic pH and the presence of the denaturant guanidine hydrochloride. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Bacillus subtilis; Conjugated bile acid hydrolases; Ntn hydrolase; Penicillin acylase

Structural determination and chemical esterification of the sophorolipids produced by Candida bombicola grown on glucose and alpha-linolenic acid - Gupta, Reetika; Prabhune, Asmita (Biotechnology Letters, 2012)
The extracellular surface-active glycolipids produced by the yeast, Candida bombicola when grown on glucose and alpha-linolenic acid, were analyzed by HPLC with electro-spray ionization (ESI-MS) and collision-induced dissociation mass spectrometry. The analysis confirmed that the sophorolipid (SL) mixture contained three different forms of C18:3 SL molecules: free acid, lactone and a diacetylated lactone, which has not been reported previously. Also a minor amount of diacetylated lactone form of C18:1 SL was detected. Further, the SL mixture was subjected to chemical esterification reaction with sodium methoxide. The reaction product was analyzed with ESI-MS and confirmed to be the single homogenous esterified product containing C18:3 moieties in its fatty acid chain.
Keywords: Candida bombicola; Collision-induced dissociation mass spectrometry; Electrospray ionization mass spectrometry; HPLC; Linolenic acid; Sophorolipid methyl ester

Biosurfactant-sophorolipid acts in synergy with antibiotics to enhance their efficiency - Joshi-Navare, Kasturi; Prabhune, Asmita (Biomed Research International, 2013)
Sophorolipids (SLs), biosurfactants with antimicrobial properties, have been tried to address the problem of antibiotic resistance. The synergistic action of SL and antibiotics was checked using standard microdilution and spread plate methods. With Staphylococcus aureus, SL-tetracycline combination achieved total inhibition before 4 h of exposure while tetracycline alone couldnot achieve total inhibition till the end of 6 h. The inhibition caused by exposure of bacterium to SL-tetracycline mixture was similar to 25% more as compared to SL alone. In spite of known robustness of gram-negative bacteria, SL-cefaclor mixture proved to be efficient against Escherichia coli which showed similar to 48% more inhibition within 2 h of exposure as compared to cefaclor alone. Scanning electron microscopy of the cells treated with mixture revealed bacterial cell membrane damage and pore formation. Moreover, SLs being a type of asymmetric bola, they are expected to form self-assemblies with unique functionality. This led to the speculation that SLs being amphiphilic in nature can span through the structurally alike cell membrane and facilitate the entry of drug molecules.

Chemically conjugated sophorolipids on CdTe QDs: a biocompatible photoluminescence nanocomposite for theranostic applications - Singh, Pooja; Joshi, Kasturi; Guin, Debanjan; Prabhune, Asmita (RSC Advances, 2013)
Functional nontoxic cadmium telluride (CdTe) quantum dots (QDs) have been synthesized using a natural functional glycolipid belonging to the family of sophorolipids (SL) as a surface-modifying agent. These SLs with open acidic form are highly suitable for QDs stabilization, are readily obtained by a fermentation process of the yeast Candida bombicola (polymorph Starmerella bombicola) in large amounts. In this work chemically stable, water soluble, and photoluminescent CdTe QDs were successfully conjugated to sophorolipids via a cross-linking reaction. The formation of SLs conjugated CdTe QDs was confirmed using different analytical techniques X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR), Transmission Electron Microscopy (TEM), Electron Diffraction (ED), Atomic Force Microscopy (AFM), Dynamic Light Scattering (DLS), and Photoluminescence (PL). It was shown that after being conjugated with SL the SL-CdTe QDs becomes biocompatible, still maintaining its water solubility and photoluminescence properties. The final SL coated photoluminescent CdTe QDs represent interesting biocompatible materials potentially useful for biomedical applications.

Crystalline xylitol production by a novel yeast, pichia caribbica (HQ222812), and its application for quorum sensing inhibition in gram-negative marker strain chromobacterium violaceum CV026 - Mukherji, Ruchira; Joshi-Navare, Kasturi; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2013)
Xylitol, a sugar alcohol, is fast gaining ground over other artificial sugar substitutes owing to its advantageous properties. Xylitol is a safer alternative for diabetics because of insulin-independent metabolism. It has beneficial properties suitable to form an important part of odontological formulations. Conventional commercial production of xylitol involves harsh chemical method operating at high temperature and pressure. Thus, microbial production of xylitol is preferred over chemical method, and yeasts have been extensively exploited for this purpose. In the present manuscript, quantitative production of xylitol from d-xylose with the yield of 0.852 gm/gm and volumetric productivity of 1.83 gm/l/h in crystalline form, using novel yeast Pichia caribbica is reported. Also, a mild, safe procedure for product extraction is described. The ability of xylitol to act as a quorum sensing antagonist in gram-negative marker strain Chromobacterium violaceum CV026 has been demonstrated for the first time.
Keywords: Crystallization; CV026; Pichia caribbica; Quorum sensing antagonist; xylitol

Evaluation of ethanol production by a new isolate of yeast during fermentation in synthetic medium and sugarcane bagasse hemicellulosic hydrolysate - Hande, Aparna; Mahajan, Siddharth A.; Prabhune, Asmita (Annals of Microbiology, 2013)
A new xylose fermenting yeast was isolated from over-ripe banana by enrichment in xylose-containing medium. The phylogenetic analysis of ITS1-5.8S-ITS2 region sequences of ribosomal RNA of isolate BY2 revealed that it shows affiliation to genus Pichia and clades with Pichia caribbica. In batch fermentation, Pichia strain BY2 fermented xylose, producing 15 g l(-1) ethanol from 30 g l(-1) xylose under shaking conditions at 28A degrees C, with ethanol yield of 0.5 g g(-1) and volumetric productivity of 0.31 g l(-1) h(-1). The optimum pH range for ethanol production from xylose by Pichia strain BY2 was 5-7. Pichia strain BY2 also produced 6.08 g l(-1) ethanol from 30 g l(-1) arabinose. Pichia strain BY2 can utilize sugarcane bagasse hemicellulose acid hydrolysate for alcohol production, efficiency of fermentation was improved by neutralization, and sequential use of activated charcoal adsorption method. Percent total sugar utilized and ethanol yield for the untreated hydrolysate was 17.14% w/v and 0.33 g g(-1), respectively, compared with 66.79% w/v and 0.45 g g(-1), respectively, for treated hemicellulose acid hydrolysate. This new yeast isolate showed ethanol yield of 0.45 g g(-1) and volumetric productivity of 0.33 g l(-1) h(-1) from sugarcane bagasse hemicellulose hydrolysate detoxified by neutralization and activated charcoal treatment, and has potential application in practical process of ethanol production from lignocellulosic hydrolysate.
Keywords: D-xylose; Ethanol; Pichia; Sugarcane bagasse hemicellulose

Fluorescent sophorolipid molecular assembly and its magnetic nanoparticle loading: a pulsed laser process - Singh, Pradeep Kumar; Mukherji, Ruchira; Joshi-Navare, Kasturi; Banerjee, Abhik; Gokhale, Rohan; Nagane, Satyawan; Prabhune, Asmita; Ogale, Satishchandra (Green Chemistry, 2013)
We report realization of strong green fluorescence in a fully biocompatible highly spherical mesoscale molecular assembly of sophorolipid created by pulsed UV laser processing of a water-based dispersion of sophorolipid. Remarkably, the said fluorescence is totally absent in the original molecule of sophorolipid and is thus the property of the pulsed laser induced modifications in the molecule and the assembly. We have separately examined the consequences of laser irradiation for glucose and oleic acid components which form the sophorolipid. This fluorescence character appears to be driven by the oleic acid component while the assembly process is assisted by the glucose component. Importantly the laser synthesized mesostructures can be easily redispersed in an aqueous medium after being dried and can also be loaded with magnetic nanoparticles (magnetite) for inducing the hyperthermia effect.

Gamma-glutamyl transferases: a structural, mechanistic and physiological perspective - Balakrishna, Sharath; Prabhune, Asmita (Frontiers in Biology, 2013)
Gamma glutamyl transferases (GGT) are highly conserved enzymes that occur from bacteria to humans. They remove terminal γ-glutamyl residue from peptides and amides. GGTs play an important role in the homeostasis of glutathione (a major cellular antioxidant) and in the detoxification of xenobiotics in mammals. They are implicated in diseases like diabetes, inflammation, neurodegenerative diseases and cardiovascular diseases. The physiological role of GGTs in bacteria is still unclear. Nothing is known about the basis for the strong conservation of the enzyme across the living system. The review focuses on the enzyme’s physiology, chemistry and structural properties of the enzyme with emphasis on the evolutionary relationships. The available data indicate that the members of the GGT family share common structural features but are functionally heterogenous.

Glucose oxidase conjugated H2O2 sensitive CdTe QDs: an effective fluorescence tool for glucose sensing - Singh, Pooja; Prabhune, Asmita; Ogale, Satishchandra B.; Guin, Debanjan (Journal of Materials Chemistry B, 2013)
Water-soluble quantum dots (QDs) are extensively used for molecular sensing because of the flexibility they offer in terms of modification of the QDs surface with a variety of functional groups using thiol chemistry and monitoring by fluorescence intensity. We describe a simple assay that allows the photoluminescence (PL) detection of H2O2 and glucose in aqueous samples and demonstrate its applicability by estimating glucose in blood. To enable the glucose detection, we functionalized the 3-mercaptopropanoic acid (MPA) capped CdTe QDs with glucose oxidase (GOx), the enzyme specific to b-D-glucose, using carbodiimide chemistry. The fluorescence of the GOx-functionalized CdTe QDs was quenched on the interaction with glucose. The same photoluminescence quenching was also observed in gel form, when a GOx modified CdTe QDs loaded agarose gel was dipped in H2O2 and glucose solutions, respectively.

Selective imaging of quorum sensing receptors in bacteria using fluorescent Au nanocluster probes surface functionalized with signal molecules - Mukherji, Ruchira; Samanta, Anupam; Illathvalappil, Rajith; Chowdhury, Somak; Prabhune, Asmita; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2013)
Fluorescent ultrasmall gold clusters decorated with bacterial quorum sensing signal molecules, acyl homoserine lactone, are synthesized. These fluorescent probes are found to have emission in the near-infrared spectral region advantageous for bioimaging. Imaging studies using different. strains of bacteria with and without acyl homoserine lactone receptors with the aid of confocal microscopy have shown that the probe interacts preferentially with cells possessing these receptors. This indicates that, with appropriate surface functionalization, the Au clusters can be used for receptor specific detection with enhanced selectivity.
Keywords: Au nanoclusters; Biosensor; fluorescence imaging; quorum sensing

Controlled release of antimicrobial Cephalexin drug from silica microparticles - Rao, B. V. Bhaskara; Mukherji, Ruchira; Shitre, G.; Alam, F.; Prabhune, Asmita; Kale, Sangeeta N. (Materials Science & Engineering C-Materials for Biological Applications, 2014)
Release of antimicrobial drugs in a controlled fashion for extended duration of time has been investigated for long. Such controlled-drug-releasing materials show promising applications in medicinal bandages. Along with antimicrobial agents, one could also incorporate other therapeutic drugs, to make such bandages more versatile. In this context, silica micro particles were synthesized using direct reduction method, in which the synthesis was done in the presence of Cephalexin. Cephalexin was chosen as an antimicrobial candidate. The morphological characterization shows formation of monodispersed, silica microparticles of similar to 200 nm in size. The FTIR spectroscopy shows weak interaction of the drug molecule at its hydroxide (OH) site with oxygen ions on the silica surface. Upon conjugation, the UV-vis spectroscopy shows persistence of the Cephalexin signature, especially its R group, confirming its antimicrobial activity even after conjugation. Loading studies reveal 12% Cephalexin loading on silica. The antimicrobial studies were done on three micro-organisms, namely, Staphylococcus aureus, Bacillus subtilis and Escherichia coli. Using zone-of-inhibition studies, it was found that E. coli, did not respond to the delivery of Cephalexin either directly or via microparticles. However, for both S. aureus and B. subtilis, the particles showed controlled release of Cephalexin for the duration of 48 h and continued maintenance and even increase in the zone of inhibition. This work demonstrates an effective protocol to prepare antimicrobial patches for controlled drug delivery. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial; Medicinal bandage; Silica microparticles; sustained drug release

Effect of pH on the hydrolytic kinetics of gamma-glutamyl transferase from bacillus subtilis - Balakrishna, Sharath; Prabhune, Asmita (Scientific World Journal, 2014)
The effect of pH on the steady state kinetics of gamma-glutamyl transferase (GGT) from Bacillus subtilis was examined using glutamyl-(3-carboxyl)-4-nitroanilide as the chromogenic reporter substrate. The enzyme was active in the pH range 7.0-11.0 with the optimum activity at pH 11.0. We noticed a pH dependent transformation in the nature of substrate consumption kinetics. The substrate saturation curves were hyperbolic in the pH range 7.0-9.0 but changed into sigmoid form at pH 10.0 and 11.0. Hill's coefficients were > 1. We also analysed the effect of pH on the structure of the enzyme. The circular dichroism spectra of the enzyme sample at pH 9.0 and 11.0 were coincidental in both far and near UV regions indicating conservation of the secondary and tertiary structures, respectively. Themolecular weight of the enzyme sample was the same in both pH 7.0 and 11.0 indicating conservation of the quaternary structure. These results show that the kinetic transformation does not involve significant conformational changes. Cooperative binding of multiple substrate molecules may not be the basis for the sigmoid kinetics as only one substrate binding site has been noticed in the reported crystal structures of B. subtilis GGT.

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2014)
Co-sonication of curcumin and acidic sophorolipid in aqueous solution is shown to lead to a dramatic enhancement of curcumin bioavailability through size reduction and encapsulation. The interaction between the two is studied and discussed based on optical absorption, photoluminescence, dynamic light scattering (DLS), zeta potential, FE-SEM, TEM, Infrared spectroscopy and X-ray diffraction measurements. The cytotoxicity effects of curcumin on breast cancer cell lines, MCF-7 and MDA-MB-231, are shown to be significantly enhanced by the formation of its complex with sophorolipid. The relative cytotoxicity of curcumin with its SL(A) complex is more due to the presence of the glucose moiety. The results further suggest that sophorolipid based formulations, which solubilize and nano-encapsulate curcumin after lipid digestion, show great potential for curcumin cell entry.

Immobilization of bile salt hydrolase enzyme on mesoporous SBA-15 for co-precipitation of cholesterol - Bhange, Pallavi; Sridevi, N.; Bhange, Deu S.; Prabhune, Asmita; Ramaswamy, Veda (International Journal of Biological Macromolecules, 2014)
We describe herein a simple and effective strategy for immobilization of bile salt hydrolase enzyme by grafting glutaraldehyde groups inside channels of APTES functionalized SBA-15. The increase in glutaraldehyde concentration prevents leakage of enzyme but showed a steep decrease in enzyme activity in the immobilized matrix. So the degree of cross-linking should be the minimum possible to ensure sufficient stability without loss of activity. Cross-linking carried out with 0.1% glutaraldehyde concentration showed the highest activity, so this was used in all further experiments. Physico-chemical characterizations of the immobilized enzyme were carried out by XRD, N-2 adsorption, TEM, FUR and Si-29 CP-MAS NMR techniques. Immobilized BSH exhibits enhanced stability over a wide pH (3-11) and temperature range (40-80 degrees C) and retains an activity even after recycling experiments and six months of storage. From our in vivo research experiment toward co-precipitation of cholesterol, we have shown that immobilized BSH enzyme may be the promising catalyst for the reduction of serum cholesterol levels in our preliminary investigation. Enhancement in pH stability at the extreme side of pH may favor the use of immobilized BSH enzyme for drug delivery purpose to with stand extreme pH conditions in the gastrointestinal conditions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Bile salt hydrolase; Co-precipitation of cholesterol; SBA-15

New role for penicillin acylases: degradation of acyl homoserine lactone quorum sensing signals by Kluyvera citrophila penicillin G acylase - Mukherji, Ruchira; Varshney, Nishant Kumar; Panigrahi, Priyabrata; Suresh, C. G.; Prabhune, Asmita (Enzyme and Microbial Technology, 2014)
Use of penicillin acylases for the production of semi-synthetic penicillins is well-known. Escherichia coli penicillin G acylase (EcPGA) has been extensively used for this purpose; however, Kluyvera citrophila penicillin G acylase (KcPGA) is assumed to be a better substitute, owing to its increased resilience to extreme pH conditions and ease of immobilization. In the present article we report a new dimension for the amidase activity of KcPGA by demonstrating its ability to cleave bacterial quorum sensing signal molecules, acyl homoserine lactones (AHL) with acyl chain length of 6-8 with or without oxo-substitution at third carbon position. Initial evidence of AHL degrading capability of KcPGA was obtained using CV026 based bioassay method. Kinetic studies performed at pH 8.0 and 50 degrees C revealed 3-oxo-C6 HSL to be the best substrate for the enzyme with V-max and K-m values of 21.37+0.85 mM/h/mg of protein and 0.1+0.01 mM, respectively. C6 HSL was found to be the second best substrate with V-max. and K-m value of 10.06+0.27 mM/h/mg of protein and 0.28+0.02 mM, respectively. Molecular modeling and docking studies performed on the active site of the enzyme support these findings by showing the fitting of AHLs perfectly within the hydrophobic pocket of the enzyme active site. (c) 2013 Elsevier Inc. All rights reserved.
Keywords: Acyl homoserine lactones; CV026; KcPGA; Quorum quenching

New yeast isolate Pichia caribbica synthesizes xylolipid biosurfactant with enhanced functionality - Joshi-Navare, Kasturi; Singh, Pradeep Kumar; Prabhune, Asmita (European Journal of Lipid Science and Technology, 2014)
Sophorolipids (SL) belong to a class of glycolipidic biosurfactants suitable for a wide range of applications. The structural diversity in SL gives rise to variation in physicochemical and biological properties. To achieve the less explored head group diversity in sophorolipid structure, a new xylose fermenting yeast Pichia caribbica has been employed for biosurfactant production. The media and fermentation parameters have been optimized to achieve maximum yield of 7.48 g/L. The physicochemical properties of the xylolipid biosurfactant have been assessed. It reduced the surface tension of distilled water from 70 to 35.9 mN/m with the low critical micellar concentration (CMC) 1.0 mg/L as compared to typical SL (reported CMC range 40-100 mg/L). Structural characterization was done using FTIR and HR-MS to identify the structure. 17-L-[(beta-D-xylopyranosyl)-oxy]-Delta 9-heptadecanoic acid correlated to m/z 415 majorly constituted the product. Control experiment was performed in which glucose was provided as the hydrophilic carbon. This product was also subjected to HR-MS analysis to determine its chemical nature and found to be different from xylolipid. Presence of xylose as head group was anticipated to give altered physicochemical and biological activities and indeed a low CMC value and better inhibitory action was demonstrated against Staphylococcus aureus. Practical applications: Sophorolipids produced by microbial sources have several advantageous properties over commercial petroleum-based surfactants including biodegradability, environmentally friendly nature, and low toxicity. Here, we have attempted to modify the hydrophilic head group by incorporating xylose in place of glucose. This molecule will also behave differently in response to different stimuli. Stimuli-responsive surfactants are a class of compounds with applications in stabilization of emulsions, suspensions or foams, drug encapsulation and delivery, hard-surface cleaning, personal care applications.
Keywords: Antibacterial action; Critical micelle concentration; Pichia caribbica; Sophorolipid; Xylolipid

Novel glycolipids synthesized using plant essential oils and their application in quorum sensing inhibition and as antibiofilm agents - Mukherji, Ruchira; Prabhune, Asmita (Scientific World Journal, 2014)
Essential oils (EOs) form an important part of traditional medicine so their anti-microbial and, in the recent past, antiquorum sensing activity has been well studied. However it is likely that due to their hydrophobic nature and reduced solubility in aqueous environments full potential of their activity cannot be realized. hence it is only rational to formulate a process to make these molecules more polar in nature. The present paper reports synthesis of sophorolipids using 12 different essential oils as substrates, thus providing surfactant-like properties to these EOs. The synthesis protocol makes the use of Candida bombicola ATCC 22214 as producer organism. The production process required 7 days of incubation at 28 degrees C and 180 rpm. Preliminary characterization of the synthesized essential oil sophorolipids (EOSLs) was performed using thin layer chromatography (TLC) and Fourier transform infrared spectroscopy (FTIR). Additionally, essential oils that were incapable of mediating quorum sensing inhibition (QSI) on their own became potent quorum sensing inhibitors upon conversion into their corresponding EOSLs. Antibiofilm potential of these EOSLs was also demonstrated using V. cholerae as test organism. Use of essential oils as substrates for glycolipid synthesis has not been attempted previously, and hence this is the first report.

From micron to nano-curcumin by sophorolipid co-processing: highly enhanced bioavailability, fluorescence, and anti-cancer efficacy (vol 4, pg 60334, 2014) - Singh, Pradeep Kumar; Wani, Kirtee; Kaul-Ghanekar, Ruchika; Prabhune, Asmita; Ogale, Satishchandra (RSC Advances, 2015)

Mechanistic understanding of rapid gelation of silk fibroin using a biosurfactant – sophorolipid - Dubey, Parul; Nawale, Laxman; Sarkar, Dhiman; Nisal, Anuya; Prabhune, Asmita (National Science Day, At CSIR-NCL, 2015)
3D polymeric hydrogels find use in biomedical applications as scaffolds and drug delivery vehicle • Silk fibroin a structural protein is a promising candidate (excellent thermo-mechanicals, biocompatibility, biodegradability) • Sophorolipid (SL)-a biosurfactant is known to exhibit antimicrobial, anti cancerous and cell differentiating. • Use of SL as gelling agent can enhance the applicability of SF hydrogels • SF-SL scaffolds obtained by lyophilization of hydrogels can find application in tissue regeneration

New class of bacterial quorum sensing antagonists: glycomonoterpenols synthesized using linalool and alpha terpineol - Mukherji, Ruchira; Prabhune, Asmita (World Journal of Microbiology & Biotechnology, 2015)
With increasing burden of antibiotic resistant microorganism search for newer drug targets and potent drug molecules is a never ending scenario. Quorum sensing (QS), the phenomenon of bacterial cross-talk, is one such target that has captured the attention of many and has been touted as the future of new age antimicrobials. Quorum sensing has the potential to regulate a plethora of bacterial virulence phenotypes and search of molecules with powerful quorum sensing inhibitory (QSI) capacity are underway. Monoterpene alcohols like linalool and alpha terpineol have been shown to possess antimicrobial and anti-biofilm activity. However in this article we attempt to bring forth a new class of compounds, glycomonoterpenols, derived from monoterpenoids alcohols. These glycomonoterpenols have been synthesized using Candida bombicola ATCC 22214 by feeding the cells with linalool and alpha terpineol respectively as substrates in 10 % glucose, production medium. The advantage of these molecules over their parent compound is their additional surfactant like property, increased solubility and enhanced QSI potential. A variety of gram-negative bacteria capable of elaborating quorum sensing mediated phenotypes have been selected and both these glycoterpenoid derivatives have been shown to possess strong anti-QS activity.
Keywords: Alpha-terpineol; Glycomonoterpenols; Linalool; Pseudomonas aeruginosa; Quorum sensing inhibition

Possible correlation between bile salt hydrolysis and ahl deamidation: staphylococcus epidermidis RM1, a potent quorum quencher and bile salt hydrolase producer - Mukherji, Ruchira; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2015)
The aim of the present work was to isolate a bile salt hydrolase (BSH) producer from fermented soy curd and explore the ability of the BSH produced to cleave bacterial quorum sensing signals. Bacterial isolates with possible ability to deconjugate bile salts were enriched and isolated on De Man, Rogosa and Sharpe (MRS) medium containing 0.2 % bile salts. BSH-producing positive isolate with orange-pink-pigmented colonies was isolated and was identified as a strain of Staphylococcus epidermidis using biochemical and phylogenetic tools. S. epidermidis RM1 was shown to possess both potent BSH and N-acyl homoserine lactone (AHL) cleavage activity. Genetic basis of this dual-enzyme activity was explored by means of specific primers designed using S. epidermidis ATCC 12228 genome as template. It was observed that a single enzyme was not responsible for both the activity. Two different genetic elements corresponding to each of the enzymatic activity were successfully amplified from the genomic DNA of the isolate.
Keywords: AHL acylase; Bile salt hydrolase; CV026; Quorum quenching; Staphylococcus epidermidis

Pulsed laser-driven molecular self-assembly of cephalexin: aggregation-induced fluorescence and its utility as a mercury ion sensor - Singh, Pradeep Kumar; Prabhune, Asmita; Ogale, Satishchandra (Photochemistry and Photobiology, 2015)
A fluorescent self-assembly of cephalexin is obtained by pulsed laser irradiation process. An intense fluorescence emission is found in the self-assembled form due to occurrence of a typical aggregation-induced emission in cephalexin molecules. It is observed that fluorescence quenching of the self-assembled fluorescent nanostructures occurs in the presence of extremely low Hg++ ions concentrations (10(-7) M) as compared to other heavy metal ions e.g. Ferrous (Fe++), Manganese (Mn++), Magnesium (Mg++), Cobalt (Co++), Nickel (Ni++) and Zinc (Zn++) at the same concentrations.

Sophorolipid assisted tunable and rapid gelation of silk fibroin to form porous biomedical scaffolds - Dubey, Parul; Nawale, Laxman; Sarkar, Dhiman; Nisal, Anuya; Prabhune, Asmita (RSC Advances, 2015)
Three dimensional polymer hydrogels, based on both natural and synthetic polymers, are increasingly being used as scaffolds and drug delivery vehicles for biomedical applications. Fibrous protein, silk fibroin (SF), obtained from the Bombyx mori silkworm is a promising candidate in this area. However, SF has a long gelation time of about a few weeks that can only be reduced by non-physiological treatments (e. g. high temperature, ultrasonication and low pH) or by addition of a chemical and non-biodegradable polymer and/or surfactant. We report here accelerated gelation of SF under physiological conditions using a biosurfactant, sophorolipid (SL) as a gelling agent. SL and SF are completely miscible and form a very clear solution upon mixing. Hence it is interesting to see that this clear solution gels in a time span of just a few hours. The hydrogels so formed have pore architecture, porosities and mechanical stability ideally suited for tissue culture applications. Here we also demonstrate that mouse fibroblast cells not only adhere to but also extensively proliferate on these SF-SL scaffolds.

UV-assisted size sampling and antibacterial screening of lantana camara leaf extract synthesized silver nanoparticles - Singh, Pradeep Kumar; Bhardwaj, Kirti; Dubey, Parul; Prabhune, Asmita (RSC Advances, 2015)
Green route synthesized silver nanoparticles are extremely toxic to multidrug resistant bacteria and have widespread applications in biomedical science. If the silver reducing weed extract possesses antimicrobial properties then it can additionally contribute to the medicinal activity. Herein, we present a synthesis of silver nanoparticles by using the weed plant Lantana camara's leaf extract. This study shows an easy, quick and cost-effective route to silver nanoparticle synthesis. Size controlled synthesis of Ag-0 nanoparticles is studied and discussed based on optical absorption, photoluminescence, dynamic light scattering (DLS), zeta potential, infrared spectroscopy, X-ray diffraction measurements, FE-SEM and TEM analysis. The synthesis of silver nanoparticles via this green approach shows very high antibacterial activity against E coli (Gram -ve) and S. aureus (Gram +ve) bacteria at a very low concentration (50 ppm Ag nanoparticles). Use of such eco-friendly nanoparticles may open a door for a new range of bactericidal agents.

Bioavailability studies of curcumin-sophorolipid nano-conjugates in the aqueous phase: role in the synthesis of uniform gold nanoparticles - Darne, Priti A.; Mehta, Mihir R.; Agawane, Sachin B.; Prabhune, Asmita (RSC Advances, 2016)
The major limiting factors for curcumin to be accepted as a modern drug, despite its widespread applications, are its low aqueous solubility, low retention time and poor bioavailability. When subjected to a mild physical stress, curcumin is observed to internalize within the micellar hydrophobic core of oleic acid sophorolipid resulting in the formation of curcumin-sophorolipid nanoconjugates (CurSL). These bio-composites show enhanced retention time and increased bioavailability of curcumin in rat models. In the presence of gold salts, CurSL act as potent reducing and capping agents, resulting in the synthesis of monodispersed, spherical gold nanoparticles (CurSL-GNPs) of 8-10 nm in size. Physicochemical, morphological and optical characteristics of both the nanoparticles are discussed based on spectroscopic absorption, photoluminescence (PL), dynamic light scattering (DLS), zeta potential, SEM and TEM measurements. FTIR spectroscopy signatures of these nanoparticles confirm the retention of functional groups in the end products. A retention time of 2 hours in blood plasma and an increase in curcumin recovery by about 150 times that previously reported were observed in the pharmacokinetic (pK(a)) studies performed on Wistar rats. The bio-distribution of gold nanoparticles in rats was studied using EDX, which revealed their presence in different vital organs. The absence of unusual legions or necrosis in histopathological analysis of vital organs in all the rat models suggests the use of curcuminsophorolipid nano-conjugates enhances curcumin bioavailability and the Cur-SL based nano-gold formulation is a good drug delivery carrier.

Biological activity of sophorolipids and their possible use as antiviral agents - Borsanyiova, Maria; Patil, Amrita; Mukherji, Ruchira; Prabhune, Asmita; Bopegamage, Shubhada (Folia Microbiologica, 2016)
Sophorolipids are surface active glycolipids consisting of a hydrophilic sophorose unit and a hydrophobic portion composed of a fatty acid tail. Crude sophorolipid sample contains both acidic and lactonic forms of sophorolipid with different degrees of acetylation and varying lengths of the fatty acid chains depending on the substrates used in the production process. Carboxylic end in the acidic form of the fatty acid is free, whereas in the lactonic form, it is internally esterified. Sophorolipids show different physicochemical properties with wide range of applications for each structural compound. Lactonic form of sophorolipids shows surface tension reducing ability and biological activity, whereas the acidic form possesses better foam forming ability and higher solubility. Presence of acetyl groups gives hydrophilic nature to the sophorolipids which promotes its antiviral and cytokine-stimulating properties. The aim of this review is to explore and suggest the plausibility of sophorolipids as therapeutic and prophylactic agents for the treatment of viral diseases.

Evaluating the anticancer activity and nanoparticulate nature of homeopathic preparations of Terminalia chebula - Wani, Kirtee; Shah, Nilesh; Prabhune, Asmita; Jadhav, Arun; Ranjekar, Prabhakar; Kaul-Ghanekar, Ruchika (Homeopathy, 2016)
Background: Breast cancer is the most common cancer diagnosed among women and is the second leading cause of cancer death. Homeopathic medicines are part of the alternative medicines that are given as a supportive therapy in breast cancer. The objective of this study was to investigate the anticancer activity of commercially available homeopathic preparations of Terminalia chebula (TC) and evaluate their nanoparticulate nature. Methods: Mother tincture (MT) and other homeopathic preparations (3X, 6C and 30C) of TC were tested for their effect on the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cell lines by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Cell growth assay was performed to analyze the effect of the different potencies on the growth kinetics of breast cancer cells. MT and 6C were evaluated for the presence of nanoparticles by using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Results: MT decreased the viability of breast cancer (MDAMB231 and MCF7) and non-cancerous (HEK 293) cells. However, the other potencies (3X, 6C and 30C) decreased the viability of only breast cancer cells without affecting the viability of the non-cancerous cells. All the potencies, MT, 3X, 6C and 30C, reduced growth kinetics of breast cancer cells, more specifically at 1:10 dilution at 24, 48 and 72 h. Under SEM, MT appeared as a mesh-like structure whereas under TEM, it showed presence of nanoclusters. On the other hand, 6C potency contained 20 nm sized nanoparticles. Conclusion: The current study reports the anticancer activity of homeopathic preparations of TC against breast cancer and reveals their nanoparticulate nature. These preliminary results warrant further mechanistic studies at both in vitro and in vivo levels to evaluate the potential of TC as nanomedicine in breast cancer.

Inhibition of quorum-sensing-mediated biofilm formation in Cronobacter sakazakii strains - Singh, Niharika; Patil, Amrita; Prabhune, Asmita; Goel, Gunjan (Microbiology-SGM, 2016)
The present study investigated plant extracts for their anti-quorum-sensing (QS) potential to inhibit the biofilm formation in Cronobacter sakazakii strains. The bioassay based on loss of pigment production by Chromobacterium violaceum 026 and Agrobacterium tumefaciens NTL4 (pZLR4) was used for initial screening of the extracts. Further, the effect of extracts on the inhibition of QS-mediated biofilm in C. sakazakii isolates was evaluated using standard crystal violet assay. The effect on biofilm texture was studied using SYTO9 staining and light and scanning electron microscopy. Among the tested extracts, Piper nigrum and Cinnamomum verum at 100 ppm resulted in 78 and 68% reduction in the production of violacein as well as blue-green colour in both biosensor strains. A higher inhibitory activity (>50 %) on biofilm formation in C. sakazakii was observed for Pip. nigrum and Cin. verum, whereas the other extracts possessed moderate (25-50 %) and minimal (<25 %) inhibitory activities. Further, the fluorescent and scanning electron microscopic images indicated a major disruption in the architecture of biofilms of tested strains by Pip. nigrum. This study points to the possibility of using Pip. nigrum and Cin. verum as inhibitor of QS-mediated biofilm formation by C. sakazakii that could be further explored for novel bioactive molecules to limit the emerging infections of C. sakazakii

Purification and partial characterization of novel penicillin V acylase from Acinetobacter sp AP24 isolated from loktak lake, an indo-burma biodiversity hotspot - Philem, Pushparani Devi; Sonalkar, Vidya V.; Dharne, Mahesh S.; Prabhune, Asmita (Preparative Biochemistry & Biotechnology, 2016)
Members of the bacterial genus Acinetobacter have attracted great attention over the past few decades, on account of their various biotechnological applications and clinical implications. In this study, we are reporting the first experimental penicillin V acylase (PVA) activity from this genus. Penicillin acylases are pharmaceutically important enzymes widely used in the synthesis of semisynthetic beta-lactam antibiotics. The bacterium, identified as Acinetobacter sp. AP24, was isolated from the water of Loktak Lake (Manipur, India), an Indo-Burma biodiversity hotspot. PVA production was increased threefold in an optimized medium with 0.2% sodium glutamate and 1% glucose as nitrogen and carbon sources respectively, after 24hr of fermentation at 28 degrees C and pH 7.0 with shaking at 180rpm. The enzyme was purified to homogeneity by cation-exchange chromatography using SP-sepharose resin. The PVA is a homotetramer with subunit molecular mass of 34 kD. The enzyme was highly specific toward penicillin V with optimal hydrolytic activity at 40 degrees C and pH 7.5. The enzyme was stable from pH 5.0 to 9.0 at 25 degrees C for 2hr. The enzyme retained 75% activity after 1hr of incubation at 40 degrees C at pH 7.5.
Keywords: 6-APA; Acinetobacter; Loktak Lake; Penicillin V acylase

Silk fibroin-sophorolipid gelation: deciphering the underlying mechanism - Dubey, Parul; Kumar, Sugam; Aswal, Vinod K.; Ravindranathan, Sapna; Rajamohanan, Pattuparambil R.; Prabhune, Asmita; Nisal, Anuya (Biomacromolecules, 2016)
Silk fibroin (SF) protein, produced by silkworm Bombyx mori, is a promising biomaterial, while sophorolipid (SL) is an amphiphilic functional biosurfactant synthesized by nonpathogenic yeast Candida bombicola. SL is a mixture of two forms, acidic (ASL) and lactonic (LSL), which when added to SF results in accelerated gelation of silk fibroin. LSL is known to have multiple biological functionalities and hence hydrogels of these green molecules have promising applications in the biomedical sector. In this work, SANS, NMR, and rheology are employed to examine the assembling properties of individual and mixed SLs and their interactions with SF to understand the mechanism that leads to rapid gelation. SANS and NMR studies show that ASL assembles to form charged micelles, while LSL forms micellar assemblies and aggregates of a mass fractal nature. ASL and LSL together form larger mixed micelles, all of which interact differently with SF. It is shown that preferential binding of LSL to SF causes rapid unfolding of the SF chain leading to the formation of intermolecular beta sheets, which trigger fast gelation. Based on the observations, a mechanism for gelation of SF in the presence of different sophorolipids is proposed.

Anti-proliferative effect of novel primary cetyl alcohol derived sophorolipids against human cervical cancer cells HeLa - Nawale, Laxman; Dubey, Parul; Chaudhari, Bhushan; Sarkar, Dhiman; Prabhune, Asmita (Plos One, 2017)
Sophorolipids (SLs) are glycolipid biosurfactants that have been shown to display anticancer activity. In the present study, we report anti-proliferative studies on purified forms of novel SLs synthesized using cetyl alcohol as the substrate (referred as SLCA) and their anticancer mechanism in human cervical cancer cells. Antiproliferative effect of column purified SLCA fractions (A, B, C, D, E and F) was examined in panel of human cancer cell lines as well as primary cells. Among these fractions, SLCA B and C significantly inhibited the survival of HeLa and HCT 116 cells without affecting the viability of normal human umbilical vein endothelial cells (HUVEC). The two fractions were identified as cetyl alcohol sophorolipids with non-hydroxylated tail differing in the degree of acetylation on sophorose head group. At an IC50 concentration SLCA B (16.32 mu g ml(-1)) and SLCA C (14.14 mu g ml(-1)) blocked the cell cycle progression of HeLa cells at G1/S phase in time-dependent manner. Moreover, SLCA B and SLCA C induced apoptosis in HeLa cells through an increase in intracellular Ca2+ leading to depolarization of mitochondrial membrane potential and increase in the caspase-3, -8 and -9 activity. All these findings suggest that these SLCAs could be explored for their chemopreventive potential in cervical cancer.

Biosynthesis of glycomonoterpenes to attenuate quorum sensing associated virulence in bacteria - Patil, Amrita; Joshi-Navre, Kasturi; Mukherji, Ruchira; Prabhune, Asmita (Biotechnology and Applied Biochemistry, 2017)
The acquisition of multidrug resistance in bacteria has become a bigger threat of late, mainly due to the bacterial signaling phenomenon, quorum sensing (QS). QS, among a population of bacteria, initiates the formation of biofilms and offers myriad advantages to bacteria. Burgeoning antibiotic resistance in biofilm-producing bacteria has motivated efforts toward finding new alternatives to these traditional antimicrobials. In the present study, we report the increased solubility and additional quorum quenching as well as biofilm disruption activity of glyco-derivatives of monoterpenes (citral and citronellal). Glycomonoterpenes of citral and citronellal were synthesized via conjugation of the monoterpenes with glucose by the non-pathogenic yeast Candida bombicola (ATCC 22214). Structural elucidation of newly synthesized glycomonoterpenes showed that one synthesized using citronellal contains three major lactonic forms with molecular weight 492.43, 473.47, and 330.39 Da whereas the one produced using citral has an acidic form with molecular weight 389.33 and 346.23 Da. The glycomonoterpenes were able to individually inhibit QS, mediated through various medium-chain and long-chain N-acyl homoserine lactones (AHLs). These new compounds are interesting additions to the known range of quorum sensing inhibitors (QSIs) and could be further explored for potential clinical applications.

Rapid synthesis of highly monodispersed silver nanoparticles from the leaves of Salvadora persica - Khan, Mamatha R. Shadab; Salunkhe, Pooja; Satpute, Shruti; Kendurkar, Shuchishweta; Prabhune, Asmita; Deval, Animesh; Chaudhari, Bhushan P. (Materials Letters, 2017)
We have demonstrated a one pot green protocol for the synthesis of highly monodispersed silver nanoparticles using leaves of Salvadora persica plant. When the leaf extract of Salvadora persica plant reacted with silver nitrate (AgNO3) solution it resulted in the synthesis of highly monodispersed silver nanoparticles with an average size of 3 nm. These nanoparticles were then completely characterized by UV-Visible spectroscopy, Transmission Electron Microscopy, Energy Dispersive Analysis of X-Rays, X-ray diffraction analysis and Fourier Transform Infrared analysis. (C) 2017 Elsevier B.V. All rights reserved.

Self-exfoliated guanidinium-based ionic covalent organic nanosheets (iCONs) - Mitra, Shouvik; Kandambeth, Sharath; Biswal, Bishnu P.; Khayum, Abdul M.; Choudhury, Chandan Kumar; Mehta, Mihir R.; Kaur, Gagandeep; Banerjee, Subhrashis; Prabhune, Asmita; Verma, Sandeep; Roy, Sudip; Kharul, Ulhas K.; et al. (Journal of the American Chemical Society, 2017)
Covalent organic nanosheets (CONs) have emerged as functional two-dimensional materials for versatile applications. Although pi-pi stacking between layers, hydrolytic instability, possible restacking prevents their exfoliation on to few thin layered CONs from crystalline porous polymers. We anticipated rational designing of a structure by intrinsic ionic linker could be the solution to produce self-exfoliated CONs without external stimuli. In an attempt to address this issue, we have synthesized three self-exfoliated guanidinium halide based ionic covalent organic nanosheets (iCONs) with antimicrobial property. Self-exfoliation phenomenon has been supported by molecular dynamics (MD) simulation as well. Intrinsic ionic guanidinium unit plays the pivotal role for both self-exfoliation and antibacterial property against both Gram-positive and Gram-negative bacteria. Using such iCONs, we have devised a Mixed matrix membrane which could be useful for antimicrobial coatings with plausible medical benefits.

pH dependent sophorolipid assemblies and their influence on gelation of silk fibroin protein - Dubey, Parul; Kumar, Sugam; Ravindranathan, Sapna; Vasudevan, Sahana; Aswal, Vinod K.; Rajamohanan, Pattuparambil R.; Nisal, Anuya; Prabhune, Asmita (Materials Chemistry and Physics, 2018)
Sophorolipid (SL), a bio-derived surfactant is an excellent gelling agent for natural fibrous protein, silk fibroin (SF) leading to potential biomedical applications. Interaction of SF with SL has been shown to accelerate the formation of hydrogel with the rate being dependent on the form of SL used. Here, we examine the effect of pH on SL-SF interaction and gel formation by employing rheology, fluorescence spectroscopy, SANS and NMR. The results indicate that the size of SL assemblies decrease as pH increases from acidic to alkaline and significantly impacts the association of SL and SF. The association of SF and SL is mainly via hydrophobic interactions, with the SL molecules forming bead like structures along the SF chain. The increased charge on the acidic form of SL at higher pH results in greater repulsion between acidic SL molecules, which are bound to the hydrophobic sites of SF, leading to rapid chain unfolding and subsequent gelation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Assemblies; Nuclear magnetic resonance spectroscopy; pH; Silk fibroin; Small angle neutron scattering; Sophorolipid

Effect of media components and growth conditions for improved linoleic acid production by beauveria species - Sanghi, Smrati; Chirmade, Tejas; More, Snehal; Prabhune, Asmita; Gupta, Vidya; Kadoo, Narendra (Journal of the American Oil Chemists Society, 2019)
Beauveria species are well-known insect pathogenic fungi, and Beauveria bassiana is used as a biopesticide against various pests in agriculture. However, the Beauveria species has not been reported as producers of microbial oils. In this study, Beauveria spp. MTCC 5184 was used to produce microbial oil with high linoleic acid (LA) content. Ten experiments were performed to evaluate the effects of several media parameters, such as carbon and nitrogen sources, pH, various concentrations of carbon and nitrogen, growth duration, and oleic acid (OLA) supplementation for maximum LA and dry biomass production by the fungus. Several of these parameters had a significant impact on the production of LA, as well as dry biomass. The glucose yeast extract (GYE) medium supplemented with 1.5% (w/v) peptone yielded maximum LA (0.32 +/- 0.01 g L-1) and biomass (5.51 +/- 0.26 g L-1). However, through the addition of 1.0% (w/v) OLA, the precursor of LA, LA production was enhanced 12-fold (1.24 +/- 0.03 g L-1), and the biomass production increased by 5-fold (11.05 +/- 0.46 g L-1) in comparison to those in the basal (GYE) medium. Using lactose as the sole carbon source produced the lowest LA (0.05 +/- 0.00 g L-1) and biomass (1.04 +/- 0.10 g L-1). The results of this study will be useful for the commercial exploitation of this fungus for the production of LA-rich microbial oil for use in the production of lubricants, greases, paints, cosmetics, etc.

Formulation and evaluation of wound healing activity of sophorolipid-sericin gel in wistar rats - More, V. Snehal; Koratkar, Santosh S.; Kadam, Navnath; Agawane, Sachin; Prabhune, Asmita (Pharmacognosy Magazine, 2019)
Sericin is a useful by-product of silk processing and is resistant to oxidation and ultraviolet and can absorb and release moisture easily. Sericin has biological activities such as antibacterial, antioxidant, and tyrosinase inhibition. Sophorolipids are microbial extracellular glycolipids produced by resting cells of Candida bombicola. Sophorolipids show excellent skin compatibility and also have antibacterial property. In this study, we have developed a novel formulation consisting of sericin and sophorolipid with calcium alginate as a binding agent. Since both the ingredients are biocompatible and biodegradable, the formulation was tested for wound healing in Wistar rats. A commercial ointment povidone was used as control. The animal group, treated with sericin and sophorolipid cream, showed fast contraction, rapid closure, and healing when compared with control and commercial ointment. These observations were validated with histopathological studies where more fibroblast proliferation, angiogenesis, and keratinization were observed. This is a green, cost-effective formulation for fast wound healing.
Keywords: Biocompatibility; formulation; sericin; Sophorolipid; wound Healing

Silk fibroin-sodium dodecyl sulfate gelation: molecular, structural, and rheological insights - Hirlekar, Swarali; Ray, Debes; Aswal, Vinod K.; Prabhune, Asmita; Nisal, Anuya; Ravindranathan, Sapna (Langmuir, 2019)
A gelling agent is necessary to accelerate sol to gel transition in an aqueous solution of silk fibroin (SF), which otherwise takes several days to complete. In this paper, we investigate the mechanism of gelation of Bornbyx mori SF by a model anionic surfactant, sodium dodecyl sulfate (SOS). Even though interactions between SDS and proteins have been extensively investigated, most of these studies have focused on globular proteins, which undergo denaturation. The interaction with a fibrous protein such as SF is different and results in an altered secondary structure leading to gelation. In this work, the concentration-dependent gelation process of the SF-SDS system is examined using rheology, SANS, FTIR, and NMR. We observed preferential binding of SDS to specific regions on the SF chain, which aids structural changes favoring beta-sheet formation. We propose a mechanism for the accelerated sol-gel transition in the SF-SDS system.

Structural and enzymatic analysis of a dimeric cholylglycine hydrolase like acylase active on N-acyl homoserine lactones - Philem, Pushparani D.; Yadav, Yashpal; Sunder, Avinash Vellore; Ghosh, Deepanjan; Prabhune, Asmita; Ramasamy, Sureshkumar (Biochimie, 2020)
The prevalence of substrate cross-reactivity between AHL acylases and beta-lactam acylases provides a glimpse of probable links between quorum sensing and antibiotic resistance in bacteria. Both these enzyme classes belong to the N-terminal nucleophile (Ntn)-hydrolase superfamily. Penicillin V acylases alongside bile salt hydrolases constitute the cholylglycine hydrolase (CGH) group of the Ntn-hydrolase superfamily. Here we report the ability of two acylases, Slac1 and Slac2, from the marine bacterium Shewanella loihica PV4 to hydrolyze AHLs. Three-dimensional structure of Slac1 reveals the conservation of the Ntn hydrolase fold and CGH active site, making it a unique CGH exclusively active on AHLs. Slac1homologs phylogenetically cluster separate from reported CGHs and AHL acylases, thereby representing a functionally distinct sub-class of CGH that might have evolved as an adaptation to the marine environment. We hypothesize that Slac1 could provide the structural framework for understanding this subclass, and further our understanding of the evolutionary link between AHL acylases and beta-lactam acylases. (C) 2020 Elsevier B.V. and Societe Francaise de Biochimie et Biologie Moleculaire (SFBBM). All rights reserved.
Keywords: AHL acylase; Cholyolglycine hydrolase; Homodimer; Ntn-fold; Shewanella loihica-PV4

Energy and life cycle impact assessment for xylitol production from corncob - Dasgupta, Diptarka; Sidana, Arushdeep; Ghosh, Prasenjit; Sharma, Tripti; Singh, Jasvinder; Prabhune, Asmita; More, Snehal; Bhaskar, Thallada; Ghosh, Debashish (Journal of Cleaner Production, 2021)
The conversion of biobased feedstocks into energy and value-added chemicals is one main approach to address the current global challenge for waste mitigation through the biorefinery mode. Corncob biomass which is one of the most abundant agricultural residue in India with a high hemicellulose content, can serve as a potential low-cost raw material for food-grade xylitol production. The present study demonstrates a process for xylitol production from corncob biomass with detailed energy and life cycle analysis for viability assessment. The major highlight of the process is the use of microbial fermentation, where biomass-derived D-xylose is converted to xylitol with high selectivity. Overall, 0.502 kg of xylitol crystals could be produced from 3.5 kg of corncob biomass. Simulation analysis revealed that the evaporators are the primary consumers of energy, and the process of heat integration can significantly reduce the energy requirements of the overall process. Environmental impacts of the system evaluated showed emission results of 8.68 kg CO2 equivalent and revealed that marine aquatic and freshwater eco-toxicity are the only possible contributors to the environment. The results suggest that the process would have favourable energy balances, which can be used in pilot plant and heat exchanger network design and operation for xylitol production scale up to 500 L. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: biomass valorization; Life cycle impact assessment; simulation; xylitol

Expression, purification and crystallization of Asrij, A novel scaffold transmembrane protein - Motiwala, Zenia; Darne, Priti; Prabhune, Asmita; Inamdar, Maneesha S.; Kulkarni, Kiran (Journal of Membrane Biology, 2021)
Asrij/OCIAD1 is a scaffold transmembrane protein belonging to the Ovarian Carcinoma Immunoreactive Antigen Domain containing protein family. In Drosophila and mouse models, Asrij localizes at the endosomal and mitochondrial membrane and is shown to regulate the stemness of hematopoietic stem cells. Interaction of Asrij with ADP Ribosylation Factor 1 (Arf1) is shown to be crucial for hematopoietic niche function and prohemocyte maintenance. Here, we report the heterologous expression, standardization of detergents and purification methodologies for crystallization of Asrij/OCIAD1. To probe the activity of bacterially expressed Asrij, we developed a protein complementation assay and conclusively show that Asrij and Arf1 physically interact. Further, we find that sophorolipids improve the solubility and monodispersibility of Asrij. Hence, we propose that sophorolipids could be novel additives for stabilization of membrane proteins. To our knowledge, this is the first study detailing methodology for the production and crystallization of a heterologously expressed scaffold membrane protein and will be widely applicable to understand membrane protein structure and function. Graphic
Keywords: Asrij/OCIAD1; Membrane protein crystallography; sophorolipids

Green antibacterial molecules: sophorolipids with varying fatty acid chain - Hirlekar, Swarali; Abhyankar, Isha; Kane, Kartiki; Trimukhe, Kalpana; Prabhune, Asmita; Nisal, Anuya (Trends in Biomaterials and Artificial Organs, 2021)
Antibiotic resistance is a rising problem of over the last decade making it difficult to treat infections caused by various pathogenic bacteria. To tackle this problem, newer antimicrobial strategies are being explored. Sophorolipids (SLs) are a class of biomolecules produced by a non-pathogenic yeast Starmarella bombicola (S. bombicold) with surfactant as well as potent broad spectrum antibacterial activity. In this work, we have successfully synthesized sophorolipids using different fatty acids with increasing chain length of hydrophobic tail; Lauric acid (C12)-LASL, Myristic acid (C14)-MASL, Palmitic acid (C16)-PASL and Stearic acid (C18)-SASL. We have used various techniques like FTIR, HRMS to characterize the synthesized SL. Further, we have measured properties like the critical micellar concentration for these biosurfactants and the SL's showed CMC less than or equal to 100 mg/L indicating excellent surface-active property. We have studied the antibacterial activity against gram-negative and gram-positive bacteria. Interestingly, the antibacterial activity was found to be more potent as the chain length of the fatty acid in the SL decreased. This trend was found to be reverse for toxicity towards mammalian cells. The shorter chain fatty acid SL's were found to be less cytotoxic. These results indicate that the sophorolipid candidates with shorter chain lengths would be beneficial for various biomedical applications such as tissue engineering, regenerative medicine and wound healing. Keywords: sophorolipid, biosurfactant, short chain fatty acid, antibacterial
Keywords: Antibacterial agents; Cells (Biology); Infection; Microbial drug resistance; Saturated fatty acids; Surface active agents

Bridging the gap: an investigation of biosurfactants-polymer systems - Abhyankar, Isha; Hirlekar, Swarali; Prabhune, Asmita; Nisal, Anuya (Current Opinion in Colloid & Interface Science, 2024)
Biosurfactants (BSs) have been extensively researched due to their potential applications in various fields, including textiles, cosmetics, pharmaceuticals, agriculture, and oil remediation. These BSs possess a diverse range of physical, chemical, and biological properties. In recent years, researchers have combined these biosurfactants with both natural and synthetic polymers, resulting in the development of advanced material systems that exhibit a unique combination of properties. This review focuses on highlighting the recent advancements in these biosurfactant-polymer material systems and identifies existing gaps in the literature. The combination of biosurfactants with polymers has led to the formation of interpenetrated hydrogels, films, chemically modified surfaces, vesicles, functionalized nanofiber nonwoven mats, nano-formulations, and nano-assemblies. Some studies have also investigated the interactions between biosurfactants and polymer molecules. In most cases, non-specific, non-covalent interactions, such as electrostatic interactions, hydrogen bonding, and hydrophobic interactions have been found to govern the properties of these systems. Moreover, promising results have been achieved through the covalent modification of polymer surfaces, followed by functionalization using biosurfactant molecules. The literature demonstrates that these advanced materials could find applications in various fields, including drug delivery, bioremediation, biomedical materials, and as antimicrobial agents. These findings indicate the promising potential of biosurfactant-polymer systems for future advancements in these areas.